2019
DOI: 10.1136/bmjophth-2018-000236
|View full text |Cite
|
Sign up to set email alerts
|

The profile of sight-threatening diabetic retinopathy in patients attending a specialist eye clinic in Hangzhou, China

Abstract: Background/aimsTo examine the profile of diabetic retinopathy, awareness and self-help in patients attending a specialist eye clinic in Hangzhou, China.MethodsA total of 199 consecutive patients with diabetes (mean age = 57 years, SD = 11) attending eye clinic at the School of Medicine, Zhejiang University, Hangzhou were examined in a cross-sectional study. Clinical/demographic data were obtained from patients’ records. Fundus photographs obtained from each patient were graded using Early Treatment of Diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
3
22
1
Order By: Relevance
“…Our finding demonstrated that, the likelihood of developing STDR was high for both types of DM participants with longer duration of diabetes (≥10 years) and this was consistent with what has been found previously in Norway, 32 Hangzhou, China, 27 mainland China, 20 India, 34 Cameroon, 41 and Malawi 29 that longer duration diabetes was associated with the development of visionthreatening diabetic retinopathy. This might be due the fact that in diabetes there are abnormalities in energy production which are thought to be the major contributor to the development of advanced diabetic complications like STDR, and these abnormalities are considered to occur late in the development of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding demonstrated that, the likelihood of developing STDR was high for both types of DM participants with longer duration of diabetes (≥10 years) and this was consistent with what has been found previously in Norway, 32 Hangzhou, China, 27 mainland China, 20 India, 34 Cameroon, 41 and Malawi 29 that longer duration diabetes was associated with the development of visionthreatening diabetic retinopathy. This might be due the fact that in diabetes there are abnormalities in energy production which are thought to be the major contributor to the development of advanced diabetic complications like STDR, and these abnormalities are considered to occur late in the development of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, our finding was lower than population-based studies done in Tanzania (23%), 26 besides the study setting the difference in the mean duration of diabetes contributed for this discrepancy. Similarly, our finding was also lower than Hangzhou, China (80%), 27 Fiji (27%), 28 and Malawi (29.4%). 29 The discrepancy could be attributed to the difference in study settings and duration of diabetes.…”
Section: Discussionmentioning
confidence: 39%
“…There are large variabilities in the reported knowledge level about DR in the literature: 37% in Australia, 65% in the USA and 27% in India [ 18 20 ]. A hospital-based study in Zhejiang and a community-based study in Liaoning, China reported that 67% and 68% of the study subjects, respectively, were unaware that diabetes can affect the eyes [ 21 , 22 ]. The differences among these studies could be partly explained by differences in health care systems, study populations and methods.…”
Section: Discussionmentioning
confidence: 99%
“…Different physical and clinical factors influence the risk of diabetic retinopathy. [ 11 ] In China, there is a significant lack of awareness of diabetes and its complications, which may affect eyes. [ 11 ] Also, the early detection of diabetic retinopathy helps in prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%